Pengembangan Aplikasi Mobile Pemesanan Dan Ketersediaan Komputer Pada Internet Cafe Jr Net Berbasis Android - Habibullah Akbar; Calvin Ramadhani Alfahrezi; Nizirwan Anwar; Muhamad Bahrul Ulum; Mukhamad Abduh (Prosiding SISFOTEK, 2021)
Internet cafe are internet services in order to be able to use them, sometimes have to queue first because of the impossible availability, so that users need a long waiting time untill the avaibility places of internet service. Many users waiting at place internet service can be bad for the company itself, because inefficiency can cause trouble for other users. Development of mobile ordering applications and the availability of computers on the internet cafe is a system that makes it easier for users to order places, and does not require a long time waiting for a computer to be available. In this case, author develops system an android application for ordering computers made with android studio software and the method used is the prototype system developer method which covers needs, planning, coding and testing. The prototype is tested based on Black Box Testing and this method is time efficient for all functional applications. The results of the black box testing prove that all the required functions can run according to the expected response, while the usability testing results produce a score 85,5 which means that is application prototype is suitable for use to make it easier for users dont want wait too long to use a computer on the internet cafe.